2019
DOI: 10.1016/j.jfda.2018.10.005
|View full text |Cite|
|
Sign up to set email alerts
|

Shenmai-Yin decreased the clearance of nifedipine in rats: The involvement of time-dependent inhibition of nifedipine oxidation

Abstract: The traditional Chinese herbal formula Shenmai-Yin (SY) and nifedipine have both been used to treat patients with cardiovascular disorders. Nifedipine is primarily oxidized by cytochrome P450 (CYP) 3A. The oxidation and pharmacokinetics of nifedipine were studied in rats in vitro and in vivo to illustrate the interaction of SY with nifedipine. Schisandrol A, schisandrin A and schisandrin B were identified as the main lignans in SY. In the study in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Histological features were also similar to those given by the group given nifedipine as a comparison. Nifedipine has been demonstrated to be useful and generally well tolerated for the treatment of stable, variable, and unstable angina, mild to severe hypertension, and Raynaud's phenomenon (Wang et al, 2019). It is an antagonist of calcium influx through slow cell membrane channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological features were also similar to those given by the group given nifedipine as a comparison. Nifedipine has been demonstrated to be useful and generally well tolerated for the treatment of stable, variable, and unstable angina, mild to severe hypertension, and Raynaud's phenomenon (Wang et al, 2019). It is an antagonist of calcium influx through slow cell membrane channels.…”
Section: Discussionmentioning
confidence: 99%
“…Five treatments were given to the rats that were identified as being pregnant: (a) normal pregnant rats (control); (b) hypertensive rats; (c) hypertensive rats + 100 mg/kg BW R. tomentosa (RHO); (d) hypertensive rats + 200 mg/kg BW R. tomentosa (RHO); and (e) hypertensive rats + 400 mg/kg BW R. tomentosa (RHO); (f) hypertensive rats + 3 mg/kg BW nifedipine (Wang et al, 2019). Under ketamine anesthesia, pregnant rats were removed on their 20 th day of gestation.…”
Section: Methodsmentioning
confidence: 99%
“…In Taiwan’s TCM prescriptions for patients with ischemic heart disease, 16% of prescriptions contained SMS, which was among the top three frequently used formulas [ 78 ]. A 1-h pretreatment of rats with SMS decreased nifedipine clearance, accompanied by decreased hepatic oxidation activity, which was primarily catalyzed by CYP3A [ 133 ]. However, 3-week repeated oral treatments with SMS suppressed rat intestinal, but not hepatic, nifedipine oxidation activity [ 134 ].…”
Section: Potential Hdis Between Tcm Formulas and Prescribed Cvd Drugsmentioning
confidence: 99%
“…The results of the in vitro inhibition study indicated the presence of time-dependent CYP3A inhibitor(s) in SMS. Among the SMS ingredients, the Schisandra lignan, schisandrin B was reported to be a PXR activator [ 136 ] but also potently inhibited rat liver microsomal CYP3A activity [ 133 ]. Although drug interactions occur in vivo , reversible and irreversible inhibition, as well as induction, may work in a complex manner.…”
Section: Potential Hdis Between Tcm Formulas and Prescribed Cvd Drugsmentioning
confidence: 99%
See 1 more Smart Citation